Effects of cocoa extract containing polyphenols and methylxanthines on biochemical parameters of obese-diabetic rats. - Mhd Jalil, Abbe Maleyki; Ismail, Amin; Chong, Pei Pei; Hamid, Muhajir; Syed Kamaruddin, Syed Hasbullah (Wiley-Blackwell, 2009)
BACKGROUND: Previous studies have indicated that cocoa extract possesses hypoglycaemic and hypocholesterolaemic properties in streptozotocin-induced diabetic rats. However, there has been limited research on the effects of cocoa extract on obese-diabetic (Ob-db) rats that mimic human diabetes syndrome. Hence this study was initiated to determine the effect of cocoa extract containing polyphenols and methylxanthines on several biochemical parameters, namely glucose level, insulin sensitivity and lipid profiles of Ob-db rats.